Association between statin treatment and LDL-cholesterol levels on the rate of ST-elevation myocardial infarction among patients with acute coronary syndromes: ACS Israeli Survey (ACSIS) 2002–2010. (1st May 2016) - Gottlieb, Shmuel; Kolker, Shimon; Shlomo, Nir; Matetzky, Shlomi; Leitersdorf, Eran; Segev, Amit; Goldenberg, Ilan; Tzivoni, Dan; Weisz, Giora; Moriel, Mady
Abstract: Background: STEMI is thought to occur as a result of a vulnerable coronary plaque rupture. Statins possess hypolipidemic and pleotropic effects that stabilize coronary plaque. We sought to determine the association between LDL-C levels, statin use prior to the index event on the type of acute coronary syndrome (ACS) presentation: STEMI vs. non-STEMI/unstable angina. Methods: Data was drawn from the ACS Israeli Survey (ACSIS), a biennial prospective survey of ACS patients hospitalized in all CCU/Cardiology departments during 2002–2010. Results: Among 6790 patients, 2760 (41%) reported statin use prior to the index ACS event. The proportion of STEMI was significantly lower among statin treated vs. statin naive patients (36% vs. 57%, p < 0.0001). At each LDL-C level, the proportion of STEMI was significantly lower only among statin treated patients (p < 0.0001). LDL-C < 70 mg/dL was associated with a lower proportion of STEMI only among statin treated but not among statin naive patients (33% vs. 57%, p < 0.0001). Multivariate analysis revealed that statin use was independently associated with a lower probability of presenting with STEMI (ORadj  = 0.73, p = 0.007), but not LDL-C < 70 mg/dL (ORadj  = 1.13, p = 0.32). Patients on high-intensity statin therapy (HIST) were less likely to present with STEMI as compared with low-intensity statin therapy (LIST) or statin naive patients (27%, 38%, 56%, respectively, p for trend < 0.0001; HIST ORadj  = 0.28, p = 0.01; LIST ORadj  = 0.48, p = 0.026). Conclusions: Among patients admitted with ACS, statin use but not LDL-C level, was associated with a lower probability of presenting with STEMI. Patients on HIST had the lowest likelihood of presenting with STEMI. Highlights: Pretreatment with statins but not LDL-C level is associated with a lower rate of STEMI presentation. This effect was more prominent with high dose statins. These findings have relevance on primary and secondary prevention.